Model Pendidikan Kader Ikatan Pelajar Muhammadiyah di Madrasah Tsanawiyah Muhammadiyah Sei Apung Jaya - Adib Anshori; Muhammad Qorib; Zuliana Zuliana (LP. Ma'arif Janggan Magetan, 2024)
The means of implementing cadre formation carried out in an organization are very important for cadres who want to know and understand more deeply about the organization. The researcher is trying to find out the model of cadre education carried out at MTs Muhammadiyah Sei Apung Jaya in the context of implementing Muhammadiyah Student Association cadre formation which is carried out for students at MTS Muhammadiyah Sei Apung Jaya. The type of research carried out is qualitative research using field research methods (field research) in which data collection is carried out through observation, interviews and documentation. It was found that the cadre education model implemented at MTs Muhammadiyah Sei Apung Jaya included MABICA as a pre-cadre activity and after the implementation of MABICA the cadres could proceed to the first cadre stage, namely PKTM I.